Micro, Small, and Medium-Sized Enterprises (MSMEs) Sustainability: The Strategic Role of Digitalization, Financial Literacy, and Technological Infrastructure - Harnida, Muthia; Vasudevan, Asokan; Mardah, Siti; Fajriyati, Ilisa; Mayvita, Prihatini Ade; Hunitie, Mohammad Faleh Ahmmad; Mohammad, Suleiman Ibrahim Shelash (Journal of Ecohumanism, 2024)
The topic of micro, small, and medium-sized enterprises has always been interesting to discuss. MSMEs contribute to the Indonesian economy but also encounter various challenges in their business operations due to the fast growth in economic development. The sustainability of micro, small, and medium-sized enterprises becomes the priority for the policymaker. Thus, to understand their problems, it is necessary to make the appropriate policy. The shifting of businesses operating in the competitive era of digitalization brings the consequences to micro, small, and medium-sized enterprises to adapt to the changes by adopting digitalization and understanding the financial literacy, and technological infrastructure to support their operation in this era. Some previous studies have found that the three factors positively and significantly influence the sustainability of MSMEs. This study takes a closer look by combining these three variables in one model to explore the impact of digitalization, financial literacy, and technological infrastructure on the sustainability of MSMEs. Data was collected from 83 owners of MSMEs in Banjarmasin, Indonesia, through an online questionnaire and analyzed using multiple linear regression. The result showing the negative effect of digitalization contradicts several previous studies that found a positive impact instead. The positive effect of financial literacy and technological infrastructure on the sustainability of MSMEs is still consistent with prior research. This research contributes to the academic insight into the importance of digitalization, financial literacy, and technological infrastructure for the sustainability of MSMEs and valuable practical recommendations to policymakers to support the sustainability of MSMEs. Further implications of these findings are discussed.